Answer:
![\sqrt{(\frac{9c^{16} }{d^{4} })^{3} }=\frac{9c^{16} }{d^{4} } \sqrt{\frac{9c^{16}}{d^{4}} } \\\\= \frac{9c^{16} }{d^{4} }.\frac{3c^{8} }{d^{2} }=\frac{27c^{24} }{d^{6} }](https://tex.z-dn.net/?f=%5Csqrt%7B%28%5Cfrac%7B9c%5E%7B16%7D%20%7D%7Bd%5E%7B4%7D%20%7D%29%5E%7B3%7D%20%20%20%7D%3D%5Cfrac%7B9c%5E%7B16%7D%20%7D%7Bd%5E%7B4%7D%20%7D%20%5Csqrt%7B%5Cfrac%7B9c%5E%7B16%7D%7D%7Bd%5E%7B4%7D%7D%20%7D%20%5C%5C%5C%5C%3D%20%20%5Cfrac%7B9c%5E%7B16%7D%20%7D%7Bd%5E%7B4%7D%20%7D.%5Cfrac%7B3c%5E%7B8%7D%20%7D%7Bd%5E%7B2%7D%20%7D%3D%5Cfrac%7B27c%5E%7B24%7D%20%7D%7Bd%5E%7B6%7D%20%7D)
=> Amelia's answer is incorrect
Step-by-step explanation:
Answer:
2.1 + 2x = 7.5
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
R(x) = -x^2+122x+400
Answer:
option (c)
Step-by-step explanation:
g.f= g(f(x))
= g(x2 -3)
= (x2 -3)+1
=x2 -2